The role of international education on public diplomacy: the case of Kosovo International Summer Academy - Labinot Hajdari; Judita Krasniqi; Blerim Limani; Emira Limani; Alex Chen (Humanities & Social Sciences Communications, 2024)
Abstract Through international education programs such as the Kosovo International Summer Academy (KSA), countries aim to change their image, influence, and shift the perception and attitudes of international students towards the host country. In this article, we analyze the role of KSA in bringing international students to Kosovo and the changes in KSA students’ perceptions, beliefs, and evaluations of Kosovo after visiting the country. We analyze the results based on how often KSA students have been to Kosovo, their most significant impressions, their attitude before and after visiting the country, and whether they would return to Kosovo after exposure to the information in KSA. Our findings suggest that after coming to Kosovo, KSA students evaluate Kosovo more positively compared to their opinion before participating in KSA. In turn, this suggests that international education programs may be a viable strategy for improving the image and public perceptions of small states facing similar state-building and diplomatic challenges as Kosovo.